304. Viral resistance analysis in the COMET-PEAK study: sotrovimab treatment in participants with mild-to-moderate COVID-19. (15th December 2022) - Yates, Phillip J; Moore, Jennifer; Han, Jennifer; Skingsley, Andrew; Schnell, Gretja; Cathcart, Andrea L; Aldinger, Melissa; Peppercorn, Amanda; Walker, Jill
Abstract: Background: Sotrovimab is a human monoclonal antibody targeting a conserved region of the SARS-CoV-2 spike (S) protein. COMET-PEAK was a 3-part, phase 2 study that evaluated intravenous (500 mg) and intramuscular (500 mg and 250 mg) administration of sotrovimab in outpatients (n=353) with mild-to-moderate COVID-19. We assessed amino acid substitutions in the SARS-CoV-2 S protein and circulating variants of concern/interest (VOC/VOI) in COMET-PEAK participants (enrolled Feb–July 2021). Methods: Mid-turbinate (Part A) or nasopharyngeal (Part B/C) samples were obtained from all participants at Baseline and Post-Baseline visits. Next generation sequencing of the SARS-CoV-2 S gene was conducted using Illumina MiSeq with a ≥5% allelic frequency cut-off for samples with a viral load above 3.0 log10 copies/mL. Baseline, post-baseline and treatment-emergent (TE) substitutions were assessed, and prevalence of VOC/VOI was evaluated. Phenotypic analyses of epitope substitutions were conducted using a pseudotyped virus assay. Results: In total, 282/353 participants had sequencing results for ≥1 visit (253 baseline, 248 post-baseline), and 219 had paired baseline and post-baseline sequences; among these, 149 (68%) had TE substitutions in the S protein (26 [12%] in the epitope). E340K was the predominant TE substitution in the epitope (15 [7%]). Across all arms 92/245 (38%) experienced virologic rebound, 8 of whom (Part A: 2; Part B: 2; Part C: 4) had TE substitutions in the epitope; none had evidence of clinical progression to severe disease. Prevalence of VOC/VOI or single amino acid substitutions of concern was 94% (266/282); the most frequent were Alpha (Part A: 8/16 [50%]; Part B: 75/128 [59%]) and Delta (Part C: 99/122 [81%]). Of 7 participants with evidence of clinical progression, none had S protein substitutions in the epitope and all had VOC/VOI (3 Alpha, 3 Delta, 1 Gamma). Sotrovimab effectively neutralized most epitope substitutions tested in vitro ; P337L and E340A/K/V conferred significantly reduced susceptibility. Conclusion: There was no evidence that sotrovimab epitope substitutions were associated with clinical progression or virologic rebound. These data are consistent with those from the COMET-ICE study. Funding Vir Biotechnology/GSK (NCT04779879). Disclosures: Phillip J Yates, PhD, GlaxoSmithKline: Employee Jennifer Moore, MD, GlaxoSmithKline: Employee Jennifer Han, MD, GlaxoSmithKline: Employee Andrew Skingsley, MD, GlaxoSmithKline: Employee|GlaxoSmithKline: Stocks/Bonds Gretja Schnell, PhD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Andrea L. Cathcart, PhD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Melissa Aldinger, PharmD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Amanda Peppercorn, MD, GlaxoSmithKline: Employee|GlaxoSmithKline: Stocks/Bonds Jill Walker, PhD, GlaxoSmithKline: Employee.